Impairment in personality functioning predicts young adult suicidal ideation and suicide attempt above and beyond depressive symptoms - Kiran Boone; Kennedy M. Balzen; Carla Sharp (Research in Psychotherapy)
Interpersonal factors and depression are believed to be some of the main drivers of suicidal thoughts and behaviors, but other factors may be equally or more important. Drawing on psychodynamic (mentalization) theory, we propose that personality functioning, in particular an incoherent sense of self, may be an important driver of suicidal thoughts and behaviors over and above factors of interpersonal functioning and depression. To evaluate this, we examined associations between personality functioning and suicidal ideation and suicide attempt in young adults. Participants (N=153; Mage=20.93) were recruited from a college sample (N=90) and a clinical sample with borderline personality disorder (N=63). Personality functioning (self and interpersonal components) was measured with the Level of Personality Functioning Scale - Brief Form 2.0. Suicidal ideation was measured with the Personality Assessment Inventory. Suicide attempt history was assessed with the Columbia-Suicide Severity Rating Scale. Depression symptoms were measured with the Symptom Checklist 90. Regressions examined relationships between personality functioning, depression symptoms, and suicidal ideation or attempt while controlling for age and gender. Overall personality functioning was significantly associated with suicidal ideation (β=.584, p<.001) and suicide attempt (β=.384, p<.001). Overall personality functioning was a stronger predictor than depression symptoms, age, and gender when included in the same model predicting suicidal ideation or attempt. Both the self and interpersonal components of personality functioning were significantly associated with suicidal ideation and attempt, with larger effect sizes for self-functioning. Findings underscore the importance of considering personality functioning, especially self-functioning, in suicide risk assessment and treatment.